2022
DOI: 10.1186/s10020-022-00454-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular landscape of IDH-mutant astrocytoma and oligodendroglioma grade 2 indicate tumor purity as an underlying genomic factor

Abstract: Background IDH-mutant astrocytoma and oligodendroglioma have an indolent natural history and are recognized as distinct entities of neoplasms. There is little knowledge on the molecular differences between IDH-mutant astrocytoma and oligodendroglioma grade 2. Therefore, we investigated the multiomics and clinical data regarding these two types of tumors. Method In silico analyses were performed around mRNA, somatic mutations, copy number alternatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…IDH-As are more heavily infiltrated by monocytic-lineage cells derived from circulation, they upregulate myeloid-cell chemotaxis genes (CSF1, FLT3LG) and upstream transcription factors (NFKB1), compared to IDH-Os ( 5 ). Moreover, immune cell (including M0, M1, and M2 macrophages) infiltration in WHO II IDH-As was generally higher than in WHO II IDH-Os, whereas T cells (CD3+, CD4+, and CD8+), cytotoxic cells, and T helper cells infiltrated in IDH-Os were significantly higher than those in IDH-As ( 14 , 15 ). Reduced tumor purity (i.e., increased invasion of glioma by non-tumor cells such as immune and stromal cells) was linked to higher malignancy and shorter survival ( 16 ).…”
Section: The Immune Microenvironment Of Isocitrate Dehydrogenase Muta...mentioning
confidence: 82%
See 1 more Smart Citation
“…IDH-As are more heavily infiltrated by monocytic-lineage cells derived from circulation, they upregulate myeloid-cell chemotaxis genes (CSF1, FLT3LG) and upstream transcription factors (NFKB1), compared to IDH-Os ( 5 ). Moreover, immune cell (including M0, M1, and M2 macrophages) infiltration in WHO II IDH-As was generally higher than in WHO II IDH-Os, whereas T cells (CD3+, CD4+, and CD8+), cytotoxic cells, and T helper cells infiltrated in IDH-Os were significantly higher than those in IDH-As ( 14 , 15 ). Reduced tumor purity (i.e., increased invasion of glioma by non-tumor cells such as immune and stromal cells) was linked to higher malignancy and shorter survival ( 16 ).…”
Section: The Immune Microenvironment Of Isocitrate Dehydrogenase Muta...mentioning
confidence: 82%
“…In gliomas, IDH mutant has been linked to reduced immunological checkpoint(PD-1, CTLA-4, LAG3, and IDO1) expression and immunosuppressive cell infiltration ( 72 , 73 ). Compared with IDH-Os, IDH-As appear to be more responsive to checkpoint immunotherapy, one reason for the relatively poor anti-checkpoint immunotherapy of IDH-Os is its reduced expression of PD-L1 and other checkpoint molecules, another reason is higher levels of T cell rejection, promoting T cell dysfunction and immunotherapy resistance ( 15 , 74 , 75 ). Berghoff et al.…”
Section: Immunotherapy Of Isocitrate Dehydrogenase Mutant Gliomamentioning
confidence: 99%
“…Differences in the TME of astrocytomas and oligodendriogliomas suggested by bulk RNA-seq studies [ 36 , 42 , 68 , 69 ] may be linked to their distinct prognosis and need to be ascertained using scRNA-seq. IDH-mutant tumors are infiltrated by a low number of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the IDH-mutated status was suggested to shape the TME, IDH-mutant astrocytomas and oligodendrogliomas differ in some genetic alterations, and exhibit different prognoses. In this regard, evaluation of TCGA and CGGA data indicated that immune infiltration is higher in astrocytomas than oligodendriogliomas [ 42 ]. Further analysis of bulk tumors using a combination of scRNA-seq and scATAC-seq approaches revealed a significant overexpression of chemotaxis factors CSF1 and FLT3LG in ATRX-mutated astrocytomas, and upregulation of CD163, a marker of immunosuppressive myeloid cells [ 43 ▪▪ ].…”
Section: The Immune Tme In Idh-mutant Gliomasmentioning
confidence: 99%
“… 27 The mode of metastasis may be associated with heterogeneous MMR status. Thus, metastasis diverges before the development of MSI, 28 because the progenitors of malignant cells do not harbor all mutations present in the primary tumor before metastatic seeding, and the tumor mutation burden of these discordant metastases is reduced. 6 However, the reason underlying MMR status heterogeneity is unknown.…”
Section: Discussionmentioning
confidence: 99%